2016
DOI: 10.1093/occmed/kqw052
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: risk factors for musculoskeletal disorders in musicians

Abstract: Because of lack of prospective studies, no causal relations could be identified in the aetiology of (playing-related) musculoskeletal disorders in instrumental musicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
69
1
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 29 publications
6
69
1
7
Order By: Relevance
“…This differs from our conclusion, since we could not identify studies that searched for risk factors using an appropriate study design. More recent systematic reviews also found methodological concerns (Baadjou et al 2016;Jacukowicz 2016;Kok et al 2016;Vervainioti and Alexopoulos 2015). In contrast to our review, the authors reported results from the subjects of each study.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…This differs from our conclusion, since we could not identify studies that searched for risk factors using an appropriate study design. More recent systematic reviews also found methodological concerns (Baadjou et al 2016;Jacukowicz 2016;Kok et al 2016;Vervainioti and Alexopoulos 2015). In contrast to our review, the authors reported results from the subjects of each study.…”
Section: Discussioncontrasting
confidence: 63%
“…Comparing our results to the literature we found seven systematic reviews about MCD in adult professional musicians (Zaza 1998;Bragge et al 2006;Wu 2007;Baadjou et al 2016;Jacukowicz 2016;Kok et al 2016;Vervainioti and Alexopoulos 2015). The presented review is the first attempt to investigate the frequencies, risk factors and treatment options for MCD in musicians.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…O resultado pode ser explicado pela capacidade da música de controlar o estresse e promover experiên-cias de recompensa, prazer e inserção social. [14][15][16] O aumento da tensão muscular decorrente da ansiedade e estresse pode promover o desenvolvimento de DTM, [17][18][19] visto que estudos comprovam que indivíduos com níveis elevados de ansiedade e depressão possuem maior risco de desenvolverem DTM em comparação a indivíduos com níveis inferiores desses sintomas. 17,20 Chisnoiu et al, 21 também sugere que a ansiedade e o estresse fazem parte da etiologia da DTM e desempenham um papel significativo em manter os sintomas ou piorá-los.…”
Section: Discussionunclassified